2017
DOI: 10.7717/peerj.3141
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of five different marine natural organic matters (NOMs) and three different metals (Cu, Pb, Zn) on early life stages of the blue mussel (Mytilus galloprovincialis)

Abstract: Metals are present in aquatic environments as a result of natural and anthropogenic inputs, and may induce toxicity to organisms. One of the main factors that influence this toxicity in fresh water is natural organic matter (NOM) but all NOMs are not the same in this regard. In sea water, possible protection by marine NOMs is not well understood. Thus, our study isolated marine NOMs by solid-phase extraction from five different sites and characterized them by excitation-emission fluorescence analysis—one insho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 67 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…In a marine diatom ( Thalassiosira weissflogii ), humic acid did not alter the amount of Pb that was internalized, although humic acid concentrations were positively related with adsorption of Pb to the exterior of the cell wall of the diatom . Nogueira et al observed that enzyme activity in embryonic Mytilus galloprovincialis was altered during 48‐h exposures to several types of natural organic matter but that the addition of metals (including Pb) did not generally alter enzyme activity beyond the effect of organic matter alone. Capodaglio et al measured complexation of Pb in seawater and found that organically complexed Pb accounted for approximately 50% of total Pb.…”
Section: Discussionmentioning
confidence: 99%
“…In a marine diatom ( Thalassiosira weissflogii ), humic acid did not alter the amount of Pb that was internalized, although humic acid concentrations were positively related with adsorption of Pb to the exterior of the cell wall of the diatom . Nogueira et al observed that enzyme activity in embryonic Mytilus galloprovincialis was altered during 48‐h exposures to several types of natural organic matter but that the addition of metals (including Pb) did not generally alter enzyme activity beyond the effect of organic matter alone. Capodaglio et al measured complexation of Pb in seawater and found that organically complexed Pb accounted for approximately 50% of total Pb.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the presence of SR-NOM the accumulation of Cu increased more obviously. NOM was previously shown to reduce metal bioavailability via chelating and sequestering metal cations (Gheorghiu et al, 2010;Al-Reasi et al, 2011;DePalma et al, 2011;Nogueira et al, 2017;Qiao et al, 2019). Nevertheless, it cannot be excluded that metal ions bound with NOM are available accumulation by aquatic organisms (Wang et al, 2016), especially for D. magna which can ingest suspended and sediment particles smaller than the reported size limit of 70 μm (Geller and Müller, 1981;Tervonen et al, 2010;Lee and Ranville, 2012).…”
Section: Single and Joint Accumulation Of Cunps And Znonps In D Magna...mentioning
confidence: 99%
“…Natural organic matter (NOM) plays an important role in modulating the ecotoxicological effects of metals (Nogueira et al, 2017) and nanoparticles (Wang et al, 2011). Previous studies have shown that the addition of NOM reduced the toxicity of metals such as Cu and Zn to aquatic organisms, due to the complexation of metal ions with NOM and thereby decreasing the bioavailability of the metals (Hyne et al, 2005;Nadella et al, 2009;Clifford and McGeer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To simulate the stable pH conditions of natural waters, a 10.0 mM sodium borate buffer solution was used to maintain pH 8.0 in all subsequent experiments. Considering the concentration of DOM in surface water, 36 EOM concentrations ranging from 1.0 to 20.0 mgC/L were used to investigate their influence on the photochemical oxidation of Mn(II).…”
Section: Experimental Procedures 221 Photochemical Oxidation Of Mn(ii)mentioning
confidence: 99%